The Religious Foundations of the European Crisis - Josef Hien (JCMS: Journal of Common Market Studies, 2019)
There has been much talk about ordoliberalism recently. Scholars and the press identify it as the dominant economic instruction sheet for Germany's European crisis politics. However, by analyzing ordoliberalism only as an economic theory, the debate downplays that ordoliberalism is also an ethical theory, with strong roots in Protestant social thought. It is this rooting in Protestant social thought that makes Ordoliberalism incompatible with the socioeconomic ethics of most of the European crisis countries, whose ethics originate in Catholic and Orthodox social thought. This divergence is the source of a crisis of understanding between European nations and hinders a collective response to the Euro crisis.
Keywords: 330; religion; ordoliberalism; European integration